Climate change social learning sandbox - Jackson, Carl; Cranston, Pete; Le Borgne, Ewen (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS) through its theme on Decision Making has since 2010 been exploring what communication and learning approaches might be appropriate in this new and constantly changing context. Jointly held workshops highlighted that for problems like climate change and development it is not sufficient to direct experts to evaluate the issue and advise policymakers or affected people how to respond. Instead, we need ongoing, flexible, consultative processes that develop a collective understanding and response. develop a collective understanding and response. One of the outcomes of the workshops was the establishment of a Sandbox as a mechanism to sustain work on the ideas and activities around Climate Change Social Learning (CCSL) that had surfaced during the workshop.